Complications Following Decompressive Craniectomy - Mraček, Jan; Mork, Jan; Dostal, Jiri; Tupy, Radek; Mrackova, Jolana; Priban, Vladimir (Journal of neurological surgery. Part A, Central European neurosurgery, 2021)
BACKGROUND:  Decompressive craniectomy (DC) has become the definitive surgical procedure to manage a medically intractable rise in intracranial pressure. DC is a life-saving procedure resulting in lower mortality but also higher rates of severe disability. Although technically straightforward, DC is accompanied by many complications. It has been reported that complications are associated with worse outcome. We reviewed a series of patients who underwent DC at our department to establish the incidence and types of complications. METHODS:  We retrospectively evaluated the incidence of complications after DC performed in 135 patients during the time period from January 2013 to December 2018. Postoperative complications were evaluated using clinical status and CT during 6 months of follow-up. In addition, the impact of potential risk factors on the incidence of complications and the impact of complications on outcome were assessed. RESULTS:  DC was performed in 135 patients, 93 of these for trauma, 22 for subarachnoid hemorrhage, 13 for malignant middle cerebral artery infarction, and 7 for intracerebral hemorrhage. Primary DC was performed in 120 patients and secondary DC in 15 patients. At least 1 complication occurred in each of 100 patients (74%), of which 22 patients (22%) were treated surgically. The following complications were found: edema or hematoma of the temporal muscle (34 times), extracerebral hematoma (33 times), extra-axial fluid collection (31 times), hemorrhagic progression of contusions (19 times), hydrocephalus (12 times), intraoperative malignant brain edema (10 times), temporal muscle atrophy (7 times), significant intraoperative blood loss (6 times), epileptic seizures (5 times), and skin necrosis (4 times). Trauma (p = 0.0006), coagulopathy (p = 0.0099), and primary DC (p = 0.0252) were identified as risk factors for complications. There was no significant impact of complications on outcome. CONCLUSIONS:  The incidence of complications following DC is high. However, we did not confirm a significant impact of complications on outcome. We emphasize that some phenomena are so frequent that they can be considered a consequence of primary injury or natural sequelae of the DC rather than its direct complication.
Keywords: intrakraniální tlak; Postoperative Complications; výsledek terapie; Intracranial Pressure; lidé; Hydrocephalus; Decompressive Craniectomy; hydrocefalus; dekompresní kraniektomie; Treatment Outcome; Retrospective Studies; pooperační komplikace; Humans; retrospektivní studie